PELAYANAN YANG DILAKUKAN GURU BK DALAM MENINGKATKAN KESEHATAN MENTAL PESERTA DIDIK DILIHAT DARI ASPEK PEMAHAMAN DIRI (Studi terhadap Peserta Didik Kelas X di SMA Negeri 15 Padang) - Hasibuan, Yuni Ratna Sari (Bimbingan dan Konseling, 2014)
This research was motivated by the condition of the studentâs who undergo mentalnot yet healthy. The research aims to: 1) describe form the studentâs mental health it can beseen from aspect self comprehension. 2) describe from counseling that done to increase thestudentâs mental health it can be seen from self comprehension. This research is hoped willbe useful for other people such as counselor, the students, counseling coordinal, headmasterand other researcher. This research is descriptive quantitative research. In this research thereseach used proportionate sampling in selecting sampel , the sum of population were 283students and the sum of respondent were 74 students. In this research the researcher usedquestionnaire as instrument. Meanwhile to analyze the data the researcher used percentage.The result of this research is: 1) the form of studentâs mental health it can be seen from selfcomprehension it can be classified into good. 2) the form of counseling that was done toincrease the studentâs mental health it can be seen from self comprehension it can beclassified into very good.